Outsmarting Cyber squatters: The Role of AI in Domain Name Protection - Nayak, Partha Shankar; Mitra, Shankar Prasad; Banerjee, Ranjan; Mukherjee, Debmalya; Nath, Shuvrajit (Journal of Neonatal Surgery, 2025)
Cybersquatting, the practice of registering domain names identical or similar to trademarks with the intent to profit, poses a significant threat to businesses and individuals alike. Traditional methods of combating cybersquatting often prove insufficient in the face of evolving tactics employed by malicious actors. This research investigates the potential of artificial intelligence (AI) in revolutionizing domain name protection. By leveraging advanced machine learning algorithms and natural language processing techniques, AI-powered systems can effectively identify and mitigate cybersquatting attempts. This paper delves into the application of AI in various aspects of domain name protection, including early detection of potential cybersquatting, automated dispute resolution, and real-time monitoring of the domain name market. Through a comprehensive analysis of existing AI-based solutions and future research directions, this study aims to contribute to the development of robust and innovative strategies for safeguarding digital assets in the era of AI.